Non‐reporting of reportable deaths to the coroner: when in doubt, report. Issue 6 (16th September 2013) - Neate, Sandra L; Bugeja, Lyndal C; Jelinek, George A; Spooner, Heather M; Ding, Luke; Ranson, David L
Abstract: Objective: To better understand the non‐reporting of reportable deaths by determining the frequency and nature of reportable deaths referred to the Coroners Court of Victoria (CCOV) by the Registry of Births, Deaths and Marriages (BDM). Design and setting: Review of referrals from BDM to the CCOV between 2003 and 2011 where an external cause of death was recorded on the death certificate, with detailed review for the period 1 July 2010 to 30 June 2011. Main outcome measures: Frequency and nature of deaths referred, accuracy of cause of death recorded on death certificate, and degree of change made to cause of death after investigation. Results: Over 9 years, there were 4283 referrals (annual mean, 476). Of 656 deaths referred between 1 July 2010 and 30 June 2011, 320 (48.8%) were found to be reportable. Most causes of death related to injuries; less common were choking, deaths after medical procedures, poisoning and transport‐related deaths. Most of the deceased were women (55.9%), were aged ≥ 80 years (80.0%), and died in hospital (68.4%). In 309 cases (96.6%), the coroner changed the cause of death after investigation, with a major change in 146 (45.6%), minor change in 160 (50.0%), and deletion of comorbidities in three (0.9%). Twenty‐one cases (6.6%) were investigated further, with one proceeding to an inquest. Conclusions: Deaths referred by BDM represent a proportion of the unquantified pool of non‐reported deaths. Non‐reporting of potentially reportable deaths and inaccurate completion of death certificates have significant implications for the health system and community. Further education of medical practitioners about reportable deaths and death certificates is required. Doctors should report any death about which they have doubt.